Comprehensive immune cell analysis of human menstrual-blood-derived stem cells therapy to concanavalin A hepatitis - Zhang, Fen; Fan, Linxiao; Liu, Qiuhong; Tang, Shima; Zhang, Sainan; Xiao, Lanlan; Zhang, Lingjian; Li, Qian; Maihemuti, Nueraili; Li, Lanjuan (Frontiers in Immunology, 2022)
Autoimmune hepatitis is an autoimmune disease with increasing occurrence worldwide. The most common and convenient mouse model is the concanavalin A (ConA) mouse model. Human menstrual-blood-derived stem cells (MenSCs) have shown great potential as a type of mesenchymal stem cell for treating various diseases. Time-of-flight mass cytometry was performed in phosphate-buffered saline control (NC) group and ConA injection with or without MenSCs treatment groups, and conventional flow cytometry was used for further validation. The serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels and H&E staining depicted that MenSCs treatment could significantly alleviate ConA-induced hepatitis. The t-distributed stochastic neighbor embedding (t-SNE) analysis of nine liver samples displayed favorable cell clustering, and the NC group was significantly different from the other two groups. The proportions of CD69+ T cells, NKT cells, and PD-L1+ macrophages were notably increased by ConA injection, while MenSCs could decrease ConA-induced macrophage percentage and M1 polarization in the liver tissue. The analysis of proinflammatory factors carried out by cytometric bead array demonstrated that tumor necrosis factor alpha (TNF-α), interleukin (IL)-17A, IL-12p70, IL-6, IL-2, IL-1b, and interferon gamma (IFN-γ) were upregulated after ConA injection and then rapidly decreased at 12 h. MenSCs also played an important role in downregulating these cytokines. Here, we described the comprehensive changes in leukocytes in the liver tissue of ConA-induced hepatitis at 12 h after ConA injection and found that MenSCs rescued ConA-induced hepatitis mostly by inhibiting macrophages and M1 polarization in mouse liver.